Creating folic acid conjugated gold nanoclusters for cancer treatment - Liu, Zhimin (2019)
Gold nanoparticles and nanoclusters are widely researched due to their unique optical and electric properties and are size-limit being considered for bio-applications. These properties are predominantly distinctive in ultra-small thiol stabilized gold nanoclusters (Au NCs) and been significantly studied over the past decades. The proposed magnetic property make Au NCs a more promising candidate for bio-imaging and therapy including drug delivery and thermotherapy. However, its intrinsic magnetic property was poorly investigated. This project focuses on the investigation of biocompatible Au NCs with magnetic property.